THE CONTRIBUTIONS OF POLISH IMMIGRANTS TO THE MAKING OF AMERICA IN 1880-1924 (Sumbangan Immigran P olandia kepada Pembangunan Amerika pada Tahun 1880-1924) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRAC This study stems from a curiosity of the life of Polish immigrants in American society and the accomplishments they contributed to the United States in the last quarter of the nineteenth century and the first quarter of the twentieth century, despite the fact that they were illiterate, unskilled, poor peasants who came to this nation as immigrants for bread. It attempts to find out whether there were important and monumental contributions that Poles had made to the making of America under American prejudice and discrimination against their alien culture, religion, settlement pattern, and social pattern. The method applied in the study is library research, while the analysis of this study is made under American Studies discipline that involves theo¬ries of American Studies and interdisciplinary approach. This study em¬ploys Theories of American Studies proposed by McDowell, namely synthe¬sis of tenses (Past-Present-Future) and synthesis of knowledge. The interdis¬ciplinary approach involves different perspectives: historical, cultural, liter¬ary, economic, sociological, psychological, and anthropological. The research results show that Poles made many important cultural, economic, and social and political contributions to the development of the United States in 1880s-1920s. Polish cultural contributions were made in sport, art, education and religion. In economy, Polish contributions were in the forms of cheap labor, agricultural products: tobacco and vegetables, and entrepreneurs. Polish social and political contributions were social, chari¬table, fraternal organizations and institutions, military services and sacri¬fices in the Revolutionary War, the Civil War, and World Wars I and II.